Phosphorous Esters of 2,13-dihydroxy-7a, 14c-dihydronaphtho[1′,2′:4,5]furo [3,2-d] furan - (:unkn) unknown (Freund Publishing House Ltd, 1999)
2,13-dihydroxy-7a, 14c-dihydronaphtho[1′,2′:4,5]furo[3.2-d]furan prepared from glyoxal bisulphite and 2,7-dihydroxynaphthalene was reacted with, C6H5PCl2, C6H5POCl2 and Br-C6H4OPOCl2 to produce its phosphorous esters. The structures of the products were investigated by MS, FTIR, 1H-NMR, 13C-NMR, and 31P-NMR. Although C6H5PCl2 gave a compound with a new ring containing phosphorous atom, C6H5POCl2 and Br-C6H4OPOCl2 resulted acyclic phosphorous esters.